Developing and improving irrigation and drainage systems: selected papers from World Bank - Le Moigne, Guy ed. (World Bank WashingtonUS, 1992)
Papers cover the period 1985-1991 and are arranged according to four areas - Sectoral overview, institutional aspects, policy and research, and technology and environment. Papers related to institutional aspects describe how the public and private sectors are moving toward assuming complementary roles in the irrigation and drainage subsector. The policy and research section concentrates on how experience in different regions can be used in the formulation of lending policy. Research needs are also highlighted. The final section stresses the technical components of successful I & D projects; papers also address environmental extermalities, encompassing environmental management and mitigation of adverse effects.